Evaluating the Effect of Design and Length of Implants on Primary Stability Using Resonance Frequency Analysis: An In Vitro Study - Gülbahar Ustaoğlu; Tuğçe Paksoy; Kerem Gümüş (Selcuk Dental Journal)
Background:Primary stability (PS) is dependent on the length and diameter of the implant, micro-morphology of the implant surface, implant design, surgical procedure, bone quantity and quality.The aim of this study was to compare short and standart dental implants according to primary stability in bone type IV using Resonance frequency analysis (RFA) test equipment.Methods: Seventy two dental implants; sandblasting with large grit particles and acid etching (SLA) surface (Dentium®,SimpleLine II, Seoul, Korea), SLActive surface- (Straumann Roxolid®, Basel, Switzerland), Resorbable blast media (RBM) surface- (Implance®,Trabzon, TURKEY) with short (4-and 6-mm length) and standart dental implants (10-mm length) were placed in bovine cow ribs with bone quality similar to a type IV human bone.RFA was performed to evaluate the primary stability. The parameters of three groups were compared with the Mann–Whitney U test. Results:Implant stability quotient (ISQ)measurements of 4-mm and 6-mm length implants were similar however, 10-mm-length implants showed statistically difference inter-groups. SLActive surface in 10-mm-length implant group showed highest ISQ value (p < 0.005). When primary stability was compared in intra groups, SLA surface and RBM surface implants showed no significant difference, but 10-mm-length of SLActive surface implant showed higher ISQ value than 4-and 6-mm length (p< 0.005).Conclusion: The length and diameter of the implants might be more effective in primary stability compared to surface design and surface properties in short implants and SLActive surface implants may show better primary stabiliy in standard implants.